Implementation Of the Use of Liveworksheets Towards Improving Students' Literacy and Critical Thinking Abilities in The Science Subject of Grade 3 Of State Elementary School - Pramurinda Aulia; Nur Aisyah; Muhammad Khozinul Huda (Universitas Islam Negeri Palopo, 2025)
This study investigates the implementation of Liveworksheets as a digital learning medium in the Natural and Social Sciences (IPAS) subject for third-grade students at Elementary School, focusing on both literacy and critical thinking skills. Using a qualitative descriptive design, the participants consisted of the school principal, two classroom teachers, and 25 students. Data were collected through classroom observations, semi-structured interviews, and documentation. The findings reveal that Liveworksheets significantly enhanced students’ literacy and motivation; 76% of students showed higher engagement and improved ability to interpret texts and images. Indicators of critical thinking also emerged, such as rechecking answers, comparing information, and discussing with peers before asking for help. Teachers reported that Liveworksheets supported the delivery of diverse tasks and instant feedback, though challenges remained, including limited device availability, unstable internet, and students’ difficulty with lengthy analytical questions. These findings suggest that while Liveworksheets can serve as an innovative learning tool, successful implementation requires adequate infrastructure, teacher training, and adaptation of tasks to students’ developmental levels. The study recommends that educators integrate Liveworksheets with traditional approaches to strengthen both literacy and higher-order thinking from the early grades.